1987
DOI: 10.3758/bf03334732
|View full text |Cite
|
Sign up to set email alerts
|

Expertise and categorization

Abstract: Experts exhibit various categorization phenomena, including category abstractness, use of second-order features, big chunks, category coherence, and category gradedness. Traditional views of categorization-the classical, prototype, and exemplar views-are variously successful in explaining these phenomena. We argue that our conceptual base view is more adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
1
7
0
2
Order By: Relevance
“…Within the expert domain, advanced bird experts and fish experts produced significantly more behavioral attributes than physical attributes. This finding fits with previous descriptions of expert categorical knowledge that maintain that experts are able to categorize on the basis of abstract (deep) features, whereas novices are bound to perceptible (superficial) features (Chi, Glaser, & Farr, 1988;Chi et al, 1989;Gobbo & Chi, 1986;Honeck, Firment, & Case, 1987). Intermediate experts and novices produced comparable numbers of behavioral and physical attributes.…”
Section: Discussionsupporting
confidence: 90%
“…Within the expert domain, advanced bird experts and fish experts produced significantly more behavioral attributes than physical attributes. This finding fits with previous descriptions of expert categorical knowledge that maintain that experts are able to categorize on the basis of abstract (deep) features, whereas novices are bound to perceptible (superficial) features (Chi, Glaser, & Farr, 1988;Chi et al, 1989;Gobbo & Chi, 1986;Honeck, Firment, & Case, 1987). Intermediate experts and novices produced comparable numbers of behavioral and physical attributes.…”
Section: Discussionsupporting
confidence: 90%
“…Studies in this area investigate why certain individuals are able to develop exceptional levels of skills and knowledge in a specific domain, such as mathematics, music, or chess and aim to identify individual learning strategies and personality traits to explain the exceptional abilities of experts (Ericsson, 2005). It has, for example, been shown that experts can store more information in short-term memory (Ericsson & Chase, 1982), are better able to distinguish between important and unimportant information (Biederman & Shiffrar, 1987), can process larger amounts of information simultaneously (Chase & Simon, 1973), have more differentiated knowledge structures (Boster & Johnson, 1989), and develop more abstract categories (Honeck, Firment, & Chase, 1987) compared to non-experts. However, neither the motivation for sharing these exceptional skills nor the influence of the social context in which the sharing of expertise with others takes place has been addressed in past research.…”
Section: Expertise and Expert Statusmentioning
confidence: 99%
“…This line of research has also shown that what we know about categorization can be specific to the context and to the experiences of individuals (Honeck, Firment, and Case [], Proffitt, Coley, and Medin [], Ahn et al. []).…”
Section: Background and Theorymentioning
confidence: 99%